RealShooting: Expanding the experience of point-and-click target shooting games - Pinheiro, Émerson B.; Vidal, Creto A.; Cavalcante Neto, Joaquim B.; Melo Leite, Antônio J.; Gomes, George A. M.; Barbosa, Ícaro da S. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
Shooting games underwent several transformations throughout their long history. However, the use of light guns in shooting games has not experienced significant development in the last decade. This article proposes a laser capture solution to achieve a new interaction with regular point and click shooting games. For that, we developed an intermediate solution that can adapt gameplay with no need to modify the original games. We used four different games to evaluate the proposed solution: two titles explicitly developed to test the model, and two commercially published third-party games. We tried different weapons (toys, airsoft, 3D printed etc.), and sowed that the obtained results were very satisfactory. No loss of performance was observed in the games – all the tested games ran stably at 60 FPS. Moreover, the players did not notice any lag between the gun shot and the corresponding mouse click performed by the system.